Swords and sorcery: a structural gamification framework for higher education using role-playing game elements - Konstantinos Ntokos (Research in Learning Technology, 2019)
Students attend the first sessions of your units and then disappear, some of them forever, and some of them have no clue what is going on or they work for other units’ assessments. When it comes to providing them with formative assessment, it is not always well received as it is perceived as extra work. The purpose of this article is to define a gamification framework based on structural gamification that focuses on that weak part of your cohorts that do not engage as much, and it does that in a great way, as it embeds video game rules and role-playing into the curriculum. This is achieved through implementing game elements to the entire second-year cohort (N = 34) of computer game development students, in the unit ‘Engineering Software Systems’. The goal is to motivate and engage the at-risk students of the cohort with lower activity, attendance and involvement in the unit.